Trends in Antihypertensive Medicine Utilization in the Republic of Srpska, Bosnia and Herzegovina: An Eleven-Year Follow-Up - Kalinić, Dragan; Škrbić, Ranko; Vulić, Duško; Stojaković, Nataša; Stoisavljević-Šatara, Svjetlana; Stojiljković, Miloš P.; Marković-Peković, Vanda; Golić Jelić, Ana; Pilipović-Broćeta, Nataša; Wong, Nathan D.; Godman, Brian (Frontiers in Pharmacology, 2022)
Background. In last two decades, there have been substantial changes in the utilisation patterns of antihypertensive medicines following new clinical trials and the introduction of new treatment guidelines. The aim of this study was to analyse utilisation and prescribing patterns regarding antihypertensive medicines in the Republic of Srpska, Bosnia and Herzegovina during an 11-year follow-up according to national and European treatment guidelines. Methods. In this retrospective, observational study, medicine utilisation data were analysed between 2009-2019 period using the ATC/DDD methodology and expressed as the number of DDD/1,000 inhabitants/day (DID/TID). The medicine utilization 90% (DU90%) method was used for determine the quality of prescribing. Results. During the observed period, the use of antihypertensive medicines increased more than 3-times (125.97 DDD/TID in 2009 vs. 414.95 DDD/TID in 2019), corresponding to a rise in the prevalence of hypertensive patients from 91.7/1000 to 186.3/1000 in the same period. This was mainly driven by increased use of angiotensin converting enzyme inhibitors (69.78 DDD/TID in 2009 vs. 238.43 DDD/TID in 2019), beta blockers (11.93 DDD/TID in 2009 vs. 41.94 DDD/TID in 2019), calcium channel blockers (30.51 DDD/TID in 2009 vs. 75.32 DDD/TID in 2019), and diuretics (11.40 DDD/TID in 2009 vs. 31.80 DDD/TID in 2019). Angiotensin receptor blockers were the fastest growing group of antihypertensive medicines in this period and their utilisation increased nearly 40 times (0.65 DDD/TID in 2009 vs. 26.33 DDD/TID in 2019). Conclusions. The overall antihypertensive medicines utilisation was largely influenced by national and ESH/ESC guidelines and strongly corresponded to the positive medicine list of the national health insurance fund. Antihypertensive medicines utilisation is comparable with medicine utilisation trends in other countries.